(-1,-2) and (-1,4)
so these have same x values, but different y values, so these are on differnt sidef of circle
distanc between them is 6
6/2=3
radius=3
so move 3 units up from (-1,-2)
(-1,1)
so
if center is (h,k) and radius is r then
(x-h)^2+(y-k)^2=r^2
(-1,1) is center and r=3
(x-(-1))^2+(y-1)^2=3^2
(x+1)^2+(y-1)^2=9
Answer: 12x-3 and 2x+4
Step-by-step explanation: i don’t know if i wanted to add them together. you j distribute that’s how i got my answer.
3 x^{2} + 8x +(-4) = 0
x = <u>-b + √ b² - 4ac</u>
2a
x = <u>-8 + √ 8² - 4(3)(-4)</u>
2(3)
x = <u>-8 + √64 - 48 </u>
6
x = -<u>8 + √16
</u> 6<u>
</u>x = -<u>8 + 4 </u> x = <u>-8 - 4</u>
6 6<u>
</u>x = <u>-4 </u> x = <u>-12</u>
6 6
x =<u> -2 </u> x = -2<u>
</u> 3 <u>
</u>
(3x-4)(3x-4) is the answer because when something is squared, it's just multiplying itself by itself, this also applies to expressions.